1995
DOI: 10.1002/jbm.820290217
|View full text |Cite
|
Sign up to set email alerts
|

Human monocyte/macrophage adhesion and cytokine production on surface‐modified poly(tetrafluoroethylene/hexafluoropropylene) polymers with and without protein preadsorption

Abstract: To study surface property-dependent human monocyte adhesion and cytokine (IL-1 beta, IL-6, TNF-alpha) production, poly(tetrafluoroethylene/hexafluoropropylene) (FEP) polymer was modified to exhibit neutral, anionic, or cationic properties by incorporating amide (CONH2) and/or carboxyl (COOH) or aminoethyl amide [CONH(CH2CH2NH)nCH2CH2NH2] groups on the surface. Monocyte adhesion on surface-modified FEP polymers and cytokines released by monocytes/macrophages (MC/MO) into the culture medium were compared to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…In our study, collagen I coatings enhanced alkaline phosphatase and OCN expression levels, triggering increased osteogenic behavior, whereas laminin-1 coatings increased EGF, nestin, cadherin 1, and keratin 8 expression, directing cells toward neurogenic cell behavior. These findings confirm previous data on the effect of surface coatings on cell function [27][28][29] and suggest that surface coatings may be used to further enhance the regenerative potential of periodontal progenitors.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, collagen I coatings enhanced alkaline phosphatase and OCN expression levels, triggering increased osteogenic behavior, whereas laminin-1 coatings increased EGF, nestin, cadherin 1, and keratin 8 expression, directing cells toward neurogenic cell behavior. These findings confirm previous data on the effect of surface coatings on cell function [27][28][29] and suggest that surface coatings may be used to further enhance the regenerative potential of periodontal progenitors.…”
Section: Discussionsupporting
confidence: 90%
“…[109][110][111][112][113][114][115][116][117] These studies have shown that macrophage activation can be modulated by the surface properties, such as material surface chemistry and surface topography [118], of the biomedical polymer.…”
Section: Crosstalk Between Macrophages/fbgcs and Inflammatorymentioning
confidence: 99%
“…The surface onto which this cell population adheres has been shown to influence such secretion. 6,27,46 Our antibody array analysis revealed greater production of soluble factors by macrophages differentiated on RGD compared with those cultured on Ch-based films. Consistent with this, enhanced secretion of matrix metaloproteinases (MMPs) and TIMPs by RGD-differentiated macrophages, as well as of more cytokine production by RGD-adherent dendritic cells, has been previously described.…”
Section: Discussionmentioning
confidence: 83%
“…47 In addition, Yun et al showed that Fg preadsorbed onto poly(tetrafluoroethylene/ hexafluoropropylene) (FEP) copolymers induced higher monocyte adhesion on surfaces containing carboxyl groups compared with an FEP surface with only amine groups. 27 Moreover, preadsorption of Fg onto three distinct polymers, previously coated with poly(2-methacryloyloxyethyl phosphorylcholine [MCP]-co-n-butyl methacrylate [BMA]), affected macrophage adhesion differently, according to the substrate used. Still, the number of adherent cells diminished in comparison to uncoated polymers and TCPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation